Potential Field Based Motion Planning with Steering Control and DYC for ADAS - Nurbaiti Wahid; Hairi Zamzuri; Nurhaffizah Hassan; Mohd Azizi Abdul Rahman (Universitas Ahmad Dahlan, 2017)
In this study, the development of motion planning and control for collision avoidance driver assistance systems is presented. A potential field approach has been used in formulating the collision avoidance algorithm based on predicted vehicle motion. Then, to realize the advanced driver assistance systems (ADAS) for collision avoidance, steering control system and direct yaw moment control (DYC) is designed to follow the desired vehicle motion. Performance evaluation is conducted in simulation environment in term of its performance in avoiding the obstacles. Simulation results show that the vehicle collision avoidance assistance systems can successfully complete the avoidance behavior without colliding.